Anti-corrosive properties of polyaniline, poly(2-toluidine), and poly(aniline-co-2-toluidine)coatings on stainless steel - Hur, E.; Bereket, G.; Sahin, Y.
This study examines the use of polyaniline (PANi), poly(2-toluidine)(PT), and poly(aniline-co-2-toluidine)(co-PT)for corrosion protection of 304-stainless steel (SS)in 0.5 M HCl solution. The PANi, PT, and co-PT coatings were synthesized on SS substrates under cyclic voltammetric (CV)conditions from acetonitrile solution using tetrabuthylammonium perchlorate (TBAP)as supporting electrolyte and perchloric acid (HClO4)as acid. These coatings were characterized by CV, FTIR, and UV-vis spectroscopy. The ability of PANi, PT, and co-PT to serve as corrosion protective coatings for SS was examined by open circuit potential-time (Eocp-time), potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS)measurements. The results of this study reveal that PANi, PT, and co- PT acts as corrosion protective coatings on SS and every coating gives protection efficiency of greater than 80
Keywords: POLYANILINE; CORROSION; ELECTROPOLYMERIZATION; CONDUCTING POLYMER